2007
DOI: 10.1111/j.1461-0248.2007.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UVB radiation on marine and freshwater organisms: a synthesis through meta‐analysis

Abstract: Ultraviolet-B (UVB) radiation is a global stressor with potentially far-reaching ecological impacts. In the first quantitative analysis of the effects of UVB on aquatic organisms, we used meta-analytic techniques to explore the effects of UVB on survival and growth in freshwater and marine systems. Based on the large body of literature on the effects of UVB in aquatic systems, we predicted that UVB would have different effects in different habitats, experimental venues, trophic groups and life history stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 90 publications
(95 reference statements)
5
172
3
2
Order By: Relevance
“…There is experimental evidence that organisms fed on UVB-damaged plankton themselves suffer reduced reproductive success including fewer eggs and more deformities (Kouwenberg and Lantoine 2006). A meta-analysis from the literature on UVB effects (Bancroft et al 2007) found an overall negative effect of UVB on both survival and growth that crossed life histories, trophic groups, habitats and experimental venues.…”
Section: The Primary Mechanism--stress From Enhanced Uvbmentioning
confidence: 99%
See 1 more Smart Citation
“…There is experimental evidence that organisms fed on UVB-damaged plankton themselves suffer reduced reproductive success including fewer eggs and more deformities (Kouwenberg and Lantoine 2006). A meta-analysis from the literature on UVB effects (Bancroft et al 2007) found an overall negative effect of UVB on both survival and growth that crossed life histories, trophic groups, habitats and experimental venues.…”
Section: The Primary Mechanism--stress From Enhanced Uvbmentioning
confidence: 99%
“…There will be additional direct effects on higher-level organisms and their eggs or larvae (e.g. Bancroft et al 2007). We will compare the data with this set of assumptions for estimating the trend in the rate of damage to the biota as a function of latitude.…”
Section: Confrontation Of Simulations With Datamentioning
confidence: 99%
“…Los factores físicos tales como la salinidad y la temperatura también regulan la sucesión estacional del plancton; la radiación solar, en particular la radiación ultravioleta (RUV, 280-400 nm), tiene efectos negativos en muchos organismos acuáticos, incluyendo el zooplancton (Bancroft et al 2007). Se sabe que la RUV afecta a las tasas de comportamiento y de mortalidad en las comunidades del zooplancton (Gonçalves y Hylander 2014), y éstas a su vez estructuran las interacciones tróficas (Williamson et al 2001, Gonçalves et al 2010.…”
Section: Study Areaunclassified
“…Solar radiation, in particular ultraviolet radiation (UVR, 280-400 nm), has overall negative effects on many aquatic organisms including zooplankton (Bancroft et al 2007). UVR is known to affect both behavior and mortality rates in zooplankton communities (Gonçalves and Hylander 2014) and these in turn structure trophic interactions (Williamson et al 2001, Gonçalves et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First, similarities among aquatic ecosystems (40%) are almost as evident as differences (46%); the remaining 14% found both similarities and differences in the same study. Similarities include the effects of light (Sommaruga et al 1997, Bancroft et al 2007) and nutrient limitation (e.g., Guildford andHecky 2000, Elser et al 2007) on aquatic organisms. Second, differences that exist between aquatic ecosystems appear to reflect the local environmental context, Elser et al 2007), and C sources (e.g., Pace 1991, Amon andBenner 1996), rather than just the more obvious differences among ecosystems in organisms, salinity, or size (e.g., Seitzinger et al 1991).…”
mentioning
confidence: 99%